2015
DOI: 10.1007/s11356-015-4180-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adsorption behavior of PCDD/Fs on carbon nanotubes and activated carbons in a bench-scale dioxin generating system

Abstract: Porous carbon-based materials are commonly used to remove various organic and inorganic pollutants from gaseous and liquid effluents and products. In this study, the adsorption of dioxins on both activated carbons and multi-walled carbon nanotube was internally compared, via series of bench scale experiments. A laboratory-scale dioxin generator was applied to generate PCDD/Fs with constant concentration (8.3 ng I-TEQ/Nm(3)). The results confirm that high-chlorinated congeners are more easily adsorbed on both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Previous study (Long and Yang, 2001) demonstrated that CNTs were much better than AC in dioxin adsorption by using temperature-programmed desorption techniques. For CNTs, a removal efficiency of PCDD/Fs over 86.8% was attained at 150°C, higher than the 70.0% and 54.2% reached for two ACs (Zhou et al, 2015b). Surface-functionalized ACs are applied to adsorb and destroy dioxin indicating that different functional groups attribute to PCDD/Fs destruction, and removal efficiency was higher than 90% for all test carbons.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous study (Long and Yang, 2001) demonstrated that CNTs were much better than AC in dioxin adsorption by using temperature-programmed desorption techniques. For CNTs, a removal efficiency of PCDD/Fs over 86.8% was attained at 150°C, higher than the 70.0% and 54.2% reached for two ACs (Zhou et al, 2015b). Surface-functionalized ACs are applied to adsorb and destroy dioxin indicating that different functional groups attribute to PCDD/Fs destruction, and removal efficiency was higher than 90% for all test carbons.…”
Section: Introductionmentioning
confidence: 79%
“…All results show that graphite performs excellent on the removal of PCDD/Fs. Compared to other adsorbents, such as AC and CNTs (Long and Yang, 2001;Zhou et al, 2015b), the removal efficiency of PCDD/Fs by graphite can achieve almost 100%. It can be attributed to the unique structure of graphite except for the pore structure.…”
Section: Adsorption Mechanismmentioning
confidence: 96%
“…125 Nevertheless, the sorptive properties of these powdered CNTs are as good or better on both a mass and surface-area normalized basis than granular activated carbon sorbents. 153,154 Compared to powdered CNTs and activated carbons, where most of the carbon mass is internal and inaccessible to large sorbates, VACNTs have theoretically maximized surface areas, tunable functional groups, great accessibility to the adsorbates, intrinsic chemical stability, and, most importantly, their bulk structure integrity could result in orders of magnitude adsorption enhancement and reuse properties that are beneficial for real world applications. 4.1.3 Ion sorption.…”
Section: Adsorptionmentioning
confidence: 99%
“…Catalysts plus adsorbents (e.g., activated carbon [4,5], zeolite [6,7], and grapheme [8]) have been proven to improve the catalytic activity by capturing more reactants onto the catalyst surface for further decomposition. CNTs are one of the excellent adsorbents for chloro-aromatic compounds [5,9] and its introduction effectively elevates the low temperature catalytic activity of several composites catalysts [10][11][12], because the presence of CNTs can: (1) enlarge the adsorption capacity and adsorption affinity of catalysts [11,12]; (2) parallelly adsorb the chloro-aromatic compounds onto the surface of CNTs [13,14]; (3) optimize the physicochemical properties of composites catalysts [10,15]. However, our previous study [15] indicated that V/Ti-CNTs catalyst achieves almost total removal of chloro-aromatic compounds mainly due to the adsorption rather than real decomposition at 150 C. Therefore, the decomposition of the adsorbed reactants needs to be further accelerated when CNTs-containing composite catalyst is used in treating chloroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Inexpensive novel catalyst achieving effective decomposition of chloro‐aromatic pollutants at low temperature (≤150°C) is strongly needed, as it can avoid extra energy consumption for reheating the flue gas after bag house‐filter (160°C) into the narrow working temperature window (200–300°C) of conventional catalysts (e.g., V 2 O 5 ‐WO 3 /TiO 2 ) . Catalysts plus adsorbents (e.g., activated carbon , zeolite , and grapheme ) have been proven to improve the catalytic activity by capturing more reactants onto the catalyst surface for further decomposition. CNTs are one of the excellent adsorbents for chloro‐aromatic compounds and its introduction effectively elevates the low temperature catalytic activity of several composites catalysts , because the presence of CNTs can: (1) enlarge the adsorption capacity and adsorption affinity of catalysts ; (2) parallelly adsorb the chloro‐aromatic compounds onto the surface of CNTs ; (3) optimize the physicochemical properties of composites catalysts .…”
Section: Introductionmentioning
confidence: 99%